Role of calcium in the defense response induced by brassinosteroids in strawberry plants - Furio, Ramiro Nicolás; Martinez Zamora, Martin Gustavo; Salazar, Sergio Miguel; Coll, Yamilet; Perato, Silvia Marisa; Martos, Gustavo Gabriel; Díaz Ricci, Juan Carlos (Elsevier, 2021)
Brassinosteroids (BRs) are steroidal hormones essential for the normal growth and development of plants. The aim of this work was to study the role of calcium, in the defense response induced by two BRs e.g. BB16 and EP24, and to investigate the expression levels of defense-related genes in strawberry plants treated with these BRs. An increase in the calcium influx in response to treatment with BB16 or EP24 was observed. By comparing Fragaria vesca and Fragaria ananassa genome sequences 28 nucleotide sequences coding for calcium-sensing proteins called CMLs were predicted. Bioinformatic analyses of the sequences revealed that all of them contained the characteristic EF-hand motif of Ca2+ binding, and regulatory cis-elements related to stress. qPCR studies showed that both BB16 and EP24 cause the upregulation of selected CMLs genes e.g. FaCML1a, FaCML36, FaCML42 and FaCML45, and defense marker genes, such as PR1, ERF1 and GLS5. Results also showed that whereas BB16 induced the upregulation of MYB30, EP24 induced the upregulation of PRX27. These results provide valuable information of the response mechanisms induced by BRs and demonstrate the role of calcium in the signaling pathways induced by BRs in strawberry plants.